The L2 sequential convergence of a solution to the mass-critical NLS above the ground state. (February 2022) - Dodson, Benjamin
Abstract: In this paper we generalize a weak sequential result of Fan (2021) to a non-scattering solutions in dimension d ≥ 2 . No symmetry assumptions are required for the initial data. We build on a previous result of Dodson (2020) for one dimension.